(untitled) (Biological Sciences - PJSIR, 2022)
To investigate the effect of tillage on soil physical properties and crop yield field experiments using rice and maize were carried out at the Bangladesh Agricultural University farmland during the autumn and winter seasons of 1989 and 1990. The rice cultivars BRll and Pajam were used in the autumn season of 1989, while during the winter of 1990, BR2 rice and maize (Barnali) were cultivated. Results revealed that the bulk density values were greater due to tilling by country plough than power tiller except in the expetiment with BRll rice. Soil bulk density increased significantly with an increase of soil depth. Root density of different crops was generally greater with power tiller as compared to country plough and it decreased significantly with an increase in soil depth. There were no significant differences in rice yield and straw due to power tiller and country plough. However, maize grain yield and car length were significantly greater with country plough as compared to power tiller.